Transesterification and epoxidation of coconut oil - Gilces Zambrano, Eduardo Patricio; Moreira Mendoza, Karen Estefanía; García Muentes, Segundo Alcides; Cevallos Cedeño, Ramón Eudoro; García Bowen, Ariana Milena (Ingeniería Química y Desarrollo, 2024)
Due to the advanced demographic increase in the world, pollution and the gradual increase in the price of oil due to the depletion of natural reserves, it causes us to think and act immediately in the face of a solution to replace said fuel with profitable, productive and eco-friendly options. planet; as is biodiesel from animal and vegetable fats through transesterification. Said raw materials are also tested in the epoxidation from which products are obtained such as: intermediate elements for the production of polyurethanes, lubricants, cosmetics or as PVC stabilizers. This article presents a bibliographical review of similar studies and demonstration on a laboratory scale, where it was verified that coconut oil complied with most of the parameters of the NTE INEN 24:1973 standard, except for the percentage of acidity and moisture, making it optimal. for transesterification and epoxidation processes respectively, also complying with most of the parameters of the NTE INEN 2482:2009 standard, with the exception of the iodine value, which is suitable for the use of alternative energy. Regarding epoxidation, the values varied considerably, categorizing it in ISO viscosity grade 5 for lubricant.